Arroz à moda da casa?: a construção da primeira denominação de origem brasileira - Pinto, Nathalia Lima (2014)
The productive flexibility and the increasing importance of goods and services quality are some of the major changes that bound the current phase of capitalism. In this context, strategies capable of promoting and communicating the differentiation of commodities become increasingly relevant. Thus, the symbolic dimension and territorial bond of the goods are acquiring greater importance within the markets in the so-called economies of signs and space. In this field, several actors from the agro food system are resorting to strategies anchored in the quality that has been derived from territorial bonds as a means of differentiating their products, among which stands out the figure of Geographical Indications (GIs).Of long standing use in Europe, these figures are still relatively recent in Brazil, where they unfold in two kinds: Indication of Origin ( IP ) and Designation of Origin (DO ). Studies on Brazilian experiments have pointed out to the potential of GIs in promoting territorial development, when able to mobilize and contemplate the interests of different social actors, valuing products, practices, identities and knowledge of the territory. But it has also been pointing out to several cases in which these experiences were merely shaped as a sectoral and socially excluding strategy, benefiting a select club of actors. Thus, this research took care to investigate the experiment of the first Denomination of Brazilian Origin, the DBO of the Rice of the Northern Coast from Rio Grande do Sul. Granted in 2010, DBO certified a peninsula of 300 km between the Lagoa dos Patos lake and the Atlantic Ocean, which has unique climatic conditions for the cultivation of the irrigated rice, covering eleven cities of the Northern Coast of the RS. Thus, the objective was to describe the trajectory of construction and acquisition of the Denomination of Origin, identifying key actors, institutions and social groups involved in this process, their relationships and interests, as well as the difficulties, conflicts and potentialities wrapped in getting the Designation of Origin. Correlatively it also sought to identify eventual impact on the promotion process of territorial development on the Northern Coast of Rio Grande do Sul. For such, the research methodologically proceeded to compile and analyze the available material on secondary sources, as well as field trips to the territory of the Northern Coast of the RS for notes, field records and conducting semi-structured interviews with key informants. It is possible to be considered that the experience of the DBO of the Rice of the Northern Coast from Rio Grande do Sul has not yet reached sufficient evidence to suggest that they are promoting a process of territorial development from the GI approach, given its still markedly sectorial character, manipulated by a club of actors, so that its impact remains limited in social, economic and environmental points of view, in the field of the researched territory.